2022
DOI: 10.3389/ijph.2022.1604479
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Risk of Stillbirth, Perinatal and Neonatal Mortality in Immigrant Women

Abstract: Objectives: This study aimed to investigate the risk of stillbirth, perinatal and neonatal mortality in immigrant women compared to native-origin women in host countries.Methods: A systematic literature review and meta-analysis was conducted. Relevant studies were identified using a thorough literature search and their quality was appraised. The analysis of heterogeneous data was carried out using the random effects model and publication bias was assessed using the Harbord-test. Also, the pooled odds ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 78 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…Some studies reported that the perinatal health of immigrants were equal or better compared to the native origin population. In contrast, some studies showed that the risk of adverse pregnancy outcomes were poorer than women in the host country [ 6 7 8 9 10 11 ]. Given the lack of conclusive evidence, the aim of this systematic review and meta-analysis was to investigate the risk of adverse maternal and neonatal outcomes in immigrant women compared to native-origin women in the host country.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that the perinatal health of immigrants were equal or better compared to the native origin population. In contrast, some studies showed that the risk of adverse pregnancy outcomes were poorer than women in the host country [ 6 7 8 9 10 11 ]. Given the lack of conclusive evidence, the aim of this systematic review and meta-analysis was to investigate the risk of adverse maternal and neonatal outcomes in immigrant women compared to native-origin women in the host country.…”
Section: Introductionmentioning
confidence: 99%
“…Immigrants may have a different health trajectory and pregnancy outcomes than nonimmigrants . Accordingly, an additional analysis was completed for the corresponding main model of any upward income mobility and SMM-M or SNM-M.…”
Section: Methodsmentioning
confidence: 99%
“…Immigrants may have a different health trajectory and pregnancy outcomes than nonimmigrants. 22 , 23 , 44 , 45 Accordingly, an additional analysis was completed for the corresponding main model of any upward income mobility and SMM-M or SNM-M. Therein, the interaction term of “neighborhood income mobility between births and immigrant status” was added to each respective model.…”
Section: Methodsmentioning
confidence: 99%
“…Foreign-born women living in Sweden constitute a heterogeneous population with different experiences, backgrounds, health needs, and health-related behaviors. Moreover, foreign-born women living in Sweden are reported to experience more adverse birth outcomes 12,13 , higher levels of fear of birth 14,15 , and stillbirth 16 .…”
Section: Introductionmentioning
confidence: 99%